Amazonian coastline candy coastal in the Amapá and Pará States, Brazil - Amaral, Dário Dantas do; Prost, Maria Thereza; Bastos, Maria de Nazaré do Carmo; Costa Neto, Salustiano Vilar; Santos, João Ubiratan Moreira dos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2008)
Coastal beach vegetation in the Amazon River delta (Pará and Amapá states, Brazil) occupies an estimated area of 1000 km2, less than 0,1% of the area occupied by other types of Amazonian vegetation. This study aims to characterize beach ecosystems of the northern Brazilian states of Pará and Amapá, based on their floristic composition (including the first species checklist for the region), vegetation classification, and geomorphology, and to establish a classification of the different types of beach vegetation in Amazonian coastal areas. Ten areas of beach vegetation were investigated on the Pará and Amapá coasts. The checklist includes 365 plant species in 237 genera and 88 families, with information on life forms, popular names, predominant vegetation community, and geographical occurrences along the coast. Three phases of beach vegetation are recognized: (1) pioneer or establishment phase, (2) intermediate or transition phase, and (3) consolidation phase. Amazonian beach ecosystems are unprotected since they lie outside of any non-use conservation unit. It is urgent that they be included in protected areas because of their vulnerable and restricted floras, some species of which are threatened with local extinction due to current high levels of human exploitation of these areas.